Dorsal epidural migration of lumbar disc herniation at L3-L4 level treated by minimally invasive microtubular decompression and fixation: A case report - Samarth Mittal; Bhupendra P Bharti; Rajesh Verma; Puneet Girdhar (Indian Spine Journal, 2024)
Lumbar disc herniation with dorsal epidural migration is a rare clinical condition that can present with severe neurological deficit and cauda equina syndrome. Diagnosis poses a challenge as it mimics other dorsal epidural pathologies like tumors, cysts, and abscesses. Timely diagnosis and early surgical intervention with wide decompression can improve the neurological outcome. Minimally invasive technique has the advantage of minimal muscle damage, early rehabilitation, and equal clinical outcomes to those of standard laminectomy. In this report, we describe a case of a 63-year-old male with lumbar disc herniation at L3-L4 level with foraminal extension and dorsal epidural migration with neurological deficit managed by minimally invasive microtubular decompression and spinal stabilization.